Hierarchically Organized Ultrathin NiO Nanofibers/Highly Defective‐rGO Heteronanocomposite: An Advanced Electrode Material for Asymmetric Supercapacitors. Issue 20 (8th September 2019) - Paliwal, Mahesh Kumar; Meher, Sumanta Kumar
Abstract: Herein, defective‐rGO (D‐rGO) is endorsed as a unique conducting matrix for defect‐induced interfacial growth of ultrathin dangling‐NiO nanofibers. The physicochemical analyses corroborate added defect density on the graphene surface, defect‐induced growth of NiO, and excellent hydrophilicity of NiO/D‐rGO heteronanocomposite. Thorough electrochemical analyses of NiO/D‐rGO heteronanocomposite show high specific capacitance of 1992 F g −1, ultralow equivalent series resistance (ESR) of 1.7 Ω, and ≈92.5% retention of charge storage after 5000 galvanostatic charge–discharge (GCD) cycles. The advanced NiO/D‐rGO ‖ Bi2 O3 asymmetric supercapacitor (ASC) device delivers high areal/mass specific capacitance and exhibits outstanding rate capacitance under extreme current density conditions. The ASC device retains a significant 89.5% of areal capacitance after 5000 GCD cycles under high rate conditions. The ASC device also delivers a high energy density of ≈43.7 Wh kg −1 at a power density of ≈4799 W kg −1 and retains ≈46% of the energy density at a very high power density of ≈18 518 W kg −1 . The excellent performance of the ASC device is ascribed to defect‐induced improved bonding between D‐rGO and NiO, microstructural stability of NiO/D‐rGO, D‐rGO prompted conductivity, and "ion‐buffering‐reservoir" ‐alike behavior of the fiber assembly. The present approach is significant in developing new‐age supercapacitors for high rate applications. Abstract : Defective‐rGO (D‐rGO) is validated as a unique conducting matrix for defect‐induced interfacial growth of ultrathin dangling‐NiO nanofibers. The NiO/D‐rGO possess perfect physicochemical/electrochemical properties for enhanced supercapacitive charge storage. The advanced NiO/D‐rGO ‖ Bi2 O3 asymmetric supercapacitor device delivers outstanding rate‐capacitance, excellent charge/discharge durability, and remarkably high energy/power density under extreme rate conditions.